Rabies research in Ethiopia: A systematic review - Gelgie, A.E.; Cavalerie, Lisa; Kaba, M.; Asrat, D.; Mor, Siobhan M. (Elsevier, 2022)
Rabies is an important zoonosis in Ethiopia, where lack of research is cited as a constraint to implementation of the national rabies control strategy. We conducted a systematic review of publications and theses on rabies in Ethiopia, to document research gaps and areas of knowledge saturation in relation to geographic and species focus, methods and findings. We also examined funding sources and extent of local researcher participation. After screening titles and abstracts, the full text of 119 publications was included in data extraction. More than 40% of publications involved data collection in one region (Oromia); no publications reported findings from Benishangul-Gumuz, Dire Dawa or Gambella. Dogs and wildlife (especially Canis simensis) were the focus of research in 45% and 24% publications, respectively. Descriptive epidemiology (N = 39 publications), ethno-medicine/−pharmacology (N = 17) and knowledge, attitude, and practice surveys (KAP, N = 15) were amongst the most common study designs, while studies involving economic methods (N = 3) and experimental epidemiology to test interventions (N = 3) were under-represented. Incidence surveys (N = 9) commonly used post-exposure prophylaxis administration in humans as a proxy for exposure without laboratory confirmation of the rabies status of the animal. KAP surveys tended to highlight reasonable levels of knowledge of rabies and poor practices, including overreliance on medicinal plants. International researchers were the first or last (senior) author on 42% and 58% of publications, respectively, most of which were funded by international organizations (45/72 publications reporting funding source). Based on this systematic review, we suggest more applied research is needed to address gaps in laboratory surveillance (including in humans, domestic and wild animals); identify effective ways to overcome socio-cultural and other barriers to accessing effective rabies treatments; inform best approaches to incentivizing mass dog vaccination programs; and generate local estimates of the cost-benefit and cost-effectiveness of different control strategies to improve financing and political buy-in for rabies control in Ethiopia.